PERBANDINGAN KEBIASAAN BERPIKIR DAN HASIL BELAJAR MATEMATIK ANTARA SISWA SANTRI DAN NON-SANTRI - Santi Arum Puspita Lestari; Dwi Sulistya Kusumaningrum (KALAMATIKA Jurnal Pendidikan Matematika, 2019)
This study aims to examine differences in mathematical habits of mind and mathematical learning outcomes between santri students and non-santri students. The design of this study is comparative research. The research data was collected by interviewing a mathematics teacher and spreading the scale of mathematical habits of mind. This research was conducted in two schools in Karawang precisely in Rawamerta. The schools used are private schools run by pesantren foundations for the sample of santri students and public schools as samples of non-santri students. From the results of data processing in the results obtained that there is no difference in mathematical habits of mind between santri students and non-santri students. In addition, there is no difference in mathematical learning outcomes between students of santri and non-santri. Meanwhile, there is an association between mathematical habits of mind and mathematical learning outcomes of students.